Nanoparticles: a New Approach to the Diagnosis and Treatment of Cerebral Glial Tumours - I. F. Gareev; O. A. Beylerli; V. N. Pavlov; Shiguang Zhao; Xin Chen; Zhixing Zheng; Chen Shen; Jinxian Sun (Креативная хирургия и онкология)
Glial tumors, and in particular anaplastic astrocytomas and glioblastoma multiforme (GBM), are aggressive brain tumors with poor prognosis and high recurrence rates. Current treatment strategies are based on open surgery, chemotherapy and radiation therapy. However, not a single one of these methods of treatment, alone or in combination, is effective in combating this disease, resulting in the average life expectancy following the diagnosis of under 15 months. Treatments are inefficient mainly due to the blood-brain barrier (BBB) that makes the delivery of drugs into the tumor mass difficult. With the development of nanotechnology the effectiveness of the drugs currently in use is on an increase and the reach to glial brain tumors is expanding. Nanoparticles are a preferred carrier of medicinal agents and dyes due to their size, availability of surface modification and the flexibility enabling the integration of several functional components into a single system. This makes it possible to direct the development of nanoparticles towards applications in the treatment and diagnosis of glial tumors. This dual approach helps to understand the location of the tumor tissue, bio-distribution of nanoparticles, and treatment progress and effectiveness. In order to improve the treatment and diagnosis approaches, various strategies can be applied to modify the surface of nanoparticles, including surface markers or so-called ligands and use the characteristics of the tumor microenvironment with specific targets which respond to specific stimuli. In this paper we review various strategies for the improvement of treatment and diagnosis of glial tumors, describe some surface markers and talk about opportunities for the introduction of nanoparticles into everyday clinical practice.